Computing in the Information Age / Second Edition - Stern Nancy; Stern Robert (John Wiley And Sons, Inc, 1996)
Introduction: The Basics, The Basics of Computing: Hardware and Software and Connectivity and People, From Micros to Mammoths, Using Productivity Tools, Hardware Advances the Information Age, Computer Processing, Input and Output: From Applications to Hardware, Secondary Storage Devices, Software Drives the Information Age, Application Packages: Beyond Basic Productivity Tools, Developing Custom Software, Systems Software, Connectivity Unites the Information Age, Connectivity and Networks and the Information Superhighway, People Power Makes the World a Better Place, Systems Analysis and Design, Database Management Information Systems, Social Issues in Computing, Appendix, An Overview of the History of Computing, Glossary, Index.
Introduction: The Basics, The Basics of Computing: Hardware and Software and Connectivity and People, From Micros to Mammoths, Using Productivity Tools, Hardware Advances the Information Age, Computer Processing, Input and Output: From Applications to Hardware, Secondary Storage Devices, Software Drives the Information Age, Application Packages: Beyond Basic Productivity Tools, Developing Custom Software, Systems Software, Connectivity Unites the Information Age, Connectivity and Networks and the Information Superhighway, People Power Makes the World a Better Place, Systems Analysis and Design, Database Management Information Systems, Social Issues in Computing, Appendix, An Overview of the History of Computing, Glossary, Index.